Studying the possibility of new Azo dye on raw canvas surface and means of dyeing process - noor al muswai; Hana Khazal Abed ALGhreeb (Al-Qadisiyah Journal of Pure Science, 2021)
A new dye AZO 4-antipyl azo (benzoic acid) was prepared. The possibility of adsorption of the water solution to the dye was studied on a raw white cloth surface where the cloth was treated and the impurities removed Before conducting adsorption experiments. The results showed that the suitable conditions for the adsorption process were in the acidic medium of the water solution of the dye. In the neutral and basal medium, the adsorption process was not induced. The effect of temperature on the adsorption process was also studied , The aim of this study was to use dye prepared in the dyeing process.